2016
DOI: 10.1007/s00253-016-7620-7
|View full text |Cite
|
Sign up to set email alerts
|

The E. coli pET expression system revisited—mechanistic correlation between glucose and lactose uptake

Abstract: Therapeutic monoclonal antibodies are mainly produced in mammalian cells to date. However, unglycosylated antibody fragments can also be produced in the bacterium Escherichia coli which brings several advantages, like growth on cheap media and high productivity. One of the most popular E. coli strains for recombinant protein production is E. coli BL21(DE3) which is usually used in combination with the pET expression system. However, it is well known that induction by isopropyl β-d-1-thiogalactopyranoside (IPTG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
85
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(86 citation statements)
references
References 51 publications
(59 reference statements)
1
85
0
Order By: Relevance
“…A batch and fed-batch phase for biomass generation were followed by an induction phase using a mixed feed medium with glucose as primary carbon source and lactose as carbon source as well as inducer. Detailed information about the bioreactor setup and media composition can be found elsewhere [32]. …”
Section: Methodsmentioning
confidence: 99%
“…A batch and fed-batch phase for biomass generation were followed by an induction phase using a mixed feed medium with glucose as primary carbon source and lactose as carbon source as well as inducer. Detailed information about the bioreactor setup and media composition can be found elsewhere [32]. …”
Section: Methodsmentioning
confidence: 99%
“…Instead, we hypothesized that the reason for this strong divergence could originate from the plasmids. All employed pET plasmids from our previous studies [20,23,24,34] were high copy number plasmids, which also carried a lacI gene, thereby introducing much more repressor protein into the cells. The GI strain however, only expressed LacI from the copies in the genome [35].…”
Section: Correlation Between Q Sglu and Q Slacmaxmentioning
confidence: 99%
“…Recent studies from our group showed that there is a correlation between the maximum specific lactose uptake rate (q s,lac,max ) and the specific glucose uptake rate (q s,glu ) in E. coli BL21 (DE3) strains carrying pET plasmids. For several different pET plasmids for expression of various products, a mechanistic model for this correlation has been established, which can serve as a basis for steering product titers, product properties and/or product location [20,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…These systems are applied in the means that the first carbon source is linked to cell growth and cell energy, whereas, the second carbon source is used to regulate recombinant protein production (Sagmeister et al 2013a). Mixed feed systems were shown to increase productivity of heterologous products (Anjou and Daugulis 2000; Jungo et al 2007; Wurm et al 2016). …”
Section: Introductionmentioning
confidence: 99%